Wymiary fundamentalizmu religijnego w ujęciu teoretycznym - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article contains an overview of selected researcher positions that make up the theory of religious fundamentalism – religious studies researchers, sociologists, political scientists and philosophers, representatives of western and Polish academic centers. Differences and divergences between their points of view the article’s author sees as value. This gives us a multifold, deepened and advanced understanding of the phenomenon, as well as an insight into which dimensions of this phenomenon is discussed and negotiated in theory of fundamentalism. Such understanding of phenomenon of fundamentalism can be useful for pedagogy of religion and general pedagogy, as referred to in the article’s conclusions.
Keywords: ideology; religious fundamentalism; social movements; theory of fundamentalism